Evaluation of autologous serum eyedrops for the treatment of experimentally induced corneal alcali burns - Gunay, C.; Sagliyan, A.; Yilmaz, S.; Kandemir, F. M.; Han, M. C.; Ozkaraca, M.; Kulualp, K. (Ecole Nationale Veterinaire Toulouse, 2015)
The aim of this study was to evaluate the clinical, biochemical and histopathological efficacy of autologous serum eyedrops for the treatment of experimentally induced corneal alkali burns in rabbits. A total of 21 New Zealand white rabbits were used as experimental animals. The rabbits were randomly allocated to three equal groups. While the first group represented the control group (n=7), the right eyes of the rabbits in the second and third groups were exposed to alkali burns with 2 N NaOH after general anesthesia. After that, while autologous serum eyedrops were instilled four times a day into the eyes of rabbits in the second group for 21 days, non-dilute autologous serum was dropped into the eyes of rabbits in the third group in a similar fashion. Schirmer test, tear break-up time (TBUT), Rose bengal and fluorescein staining methods were performed on days one, seven, 14 and 21. At the end of the treatment period, all rabbits were euthanized. Aqueous humor and cornea samples were collected to obtain biochemical and histopathological data. Significant difference was observed between the third group and the second group (P < 0,001) at the end of 21 days. Malondialdehyde (MDA), reduced glutathione (GSH) concentrations, and catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and glutathione-S-transferase (GST) activities were analyzed in the cornea and aqueous humor. Histopathological, neovascularization, polymorphonuclear leukocytes (PMNL), and epithelial thickness were measured. Statistically, neovascularization and PMNL were found to be lower in the third group compared to the second group (P < 0.05). No significant difference was found between the groups regarding the epithelial thickness. Consequently, the results of the present study showed that topical application of undiluted autologous serum eyedrops can be useful in the treatment of corneal alkali burns.
Keywords: cornea; alcali wound; autolog serum eyedrops; rabbits